Design and dynamic stiffness evaluation of magnetorheological elastomer bushing using FEMM and dynamic testing machine - Mohamad Ihsan, Abdul Hamid; Saiful Amri, Mazlan; Nur Azmah, Nordin; Abd Fatah, Abdul Yasser; Ubaidillah, U.; Imaduddin, Fitrian; Izwan, Ismail (UiTM Press, 2023)
This research presents a simulation study on electromagnetic behaviour of magnetic flux density distribution in a magnetorheological elastomer (MRE) bushing. The design concept of MRE bushing is based on the design of the bushing used in the conventional car, only the natural rubber is being replaced by the MRE compound. Furthermore, the electromagnetic simulations were conducted by using Finite Element Method Magnetics (FEMM) software where the main aim is for more magnetic flux density in the MRE, which indicates better performances for MRE bushing in this study. The best configuration of the MRE bushing for this study is using single coil, magnetic material for all parts except for coil bobbin, and the thickness of ring plate of 4 mm, which yield the highest magnetic flux density of 0.205 T. By using this configuration, the dynamic stiffness of this MRE bushing is ranging from 2259.13 N/mm to 2671.06 N/mm with the applied currents of 0.5 A to 2.5 A and frequencies from 1 Hz to 15 Hz. All in all, the optimized configurations improve the performance of MRE bushing remarkably.